HLA Profile in Iraqi Rheumatic Valvulitis Patients - Al-Hassan, Ahmed A.A.; Al-Faham, Mohammed; Al-Naseri, Sana’a; Al-Mashat, Emad; Al-Douri, Qassim; Al-Nnema, Ameera J.; Shereef, Salwa M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Human leukocyte antigen (HLA) is the most polymorphic genetic system in man. The genes of this region influence susceptibility to certain disease.Objectives: This study was established to shed light on the possible association of HLA class I and II antigens with RV patients.Patients and Methods: Lymphocytotoxicity assay for HLA for class I and II typing had been done for (100) Iraqi patients suffering from rheumatic valvulitis (RV), the control groups consisting of (75 healthy individuals and 35 non rheumatic heart disease (NRHD) patients ).Results: The results showed a significant association of A33-Ags with these patients as compared with healthy and cardiac controls (P=0.005), (P=0.033) respectively. Another interesting finding was the low frequency of A1 in RV patients when compared with healthy control (p=0.002), suggesting that A1 allele may confer protective effect against this disease. In addition significant association between blood group B and RV was evident (p=0.04). An interesting observation was a strong association of blood group B and A33 among those patients (P